Cofactor-independent C–C bond cleavage reactions catalyzed by the AlpJ family of oxygenases in atypical angucycline biosynthesis - Gao, Jinmin; Li, Liyuan; Shen, Shijie; Ai, Guomin; Wang, Bin; Guo, Fang; Yang, Tongjian; Han, Hui; Xu, Zhengren; Pan, Guohui; Fan, Keqiang (Beilstein Journal of Organic Chemistry, 2024)
Biosynthesis of atypical angucyclines involves unique oxidative B-ring cleavage and rearrangement reactions, which are catalyzed by AlpJ-family oxygenases, including AlpJ, JadG, and GilOII. Prior investigations established the essential requirement for FADH2/FMNH2 as cofactors when utilizing the quinone intermediate dehydrorabelomycin as a substrate. In this study, we unveil a previously unrecognized facet of these enzymes as cofactor-independent oxygenases when employing the hydroquinone intermediate CR1 as a substrate. The enzymes autonomously drive oxidative ring cleavage and rearrangement reactions of CR1, yielding products identical to those observed in cofactor-dependent reactions of AlpJ-family oxygenases. Furthermore, the AlpJ- and JadG-catalyzed reactions of CR1 could be quenched by superoxide dismutase, supporting a catalytic mechanism wherein the substrate CR1 reductively activates molecular oxygen, generating a substrate radical and the superoxide anion O2•−. Our findings illuminate a substrate-controlled catalytic mechanism of AlpJ-family oxygenases, expanding the realm of cofactor-independent oxygenases. Notably, AlpJ-family oxygenases stand as a pioneering example of enzymes capable of catalyzing oxidative reactions in either an FADH2/FMNH2-dependent or cofactor-independent manner.
Keywords: angucyclines; aromatic polyketide; biosynthesis; cofactor-independent oxygenase; oxidative rearrangement reaction